Cuidados de enfermería en pacientes con preeclampsia más signos de severidad - Yanzaguano Toainga, Olga Natalia (2025)
Preeclampsia plus severe symptoms is one of the most complex hypertensive disorders in clinical practice. Since if this is not treated promptly, it can be life-threatening for both the mother and the fetus. Objective: To determine nursing interventions for patients with preeclampsia plus severe symptoms. Methodology: A qualitative narrative review with a descriptive scope was conducted through an information search in databases such as Revista Scielo, the Virtual Health Library, and Google Scholar. These sources allowed access to various indexed journals, including Dialnet, PubMed, and Lilacs, as well as official websites of the World Health Organization (WHO) and the Pan American Health Organization (PAHO). Results: Preeclampsia plus severe symptoms is primarily associated with maternal conditions such as age, nulliparity, multiparity, overweight, a history of preeclampsia, and comorbidities. Complications include eclampsia, HELLP syndrome, stroke, pulmonary edema, increased incidence of cesarean sections, fetal distress and growth restriction, as well as maternal and fetal death. Conclusions: Nursing care for patients with preeclampsia plus severe symptoms should focus on the early detection of obstetric risk to prevent the progression of hypertensive disorders. This includes strict monitoring of blood pressure and other vital signs in both the mother and fetus.